Kemampuan Literasi Baca Tulis Anak Usia Dasar (Studi Analisis Perkembangan Bahasa Anak Usia 7-12 Tahun di Madrasah Ibtidaiyah (MI) Salafiyah Tajungsari Kecamatan Tlogowungu Kabupaten Pati) - Muh Syauqi Malik; Maemunah Maemunah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Indonesian people's literacy literacy is relatively low in the eyes of the international community, it can be seen from the achievements of the Indonesian state in the Program for International Student Assessment (PISA) initiated by the Organization for Economic Cooperation and Development (OECD). This scientific article aims to describe the ability to read and write literacy of elementary school children using a study of language development analysis of children aged 7-12 years at MI Salafiyah Tajungsari, Tlogowungu District, Pati Regency. The type of research used is descriptive qualitative. The data collection tool in this study uses online interviews and literature studies. The data collected was then analyzed using qualitative descriptive data analysis techniques, namely data reduction, data presentation and conclusion drawing. The results showed that children's language development can be analyzed using 4 aspects, namely phonology (sounds of language), morphology (form of words), syntax (ins and outs of sentences), and semantics (meaning of words). The results of these four aspects indicate that MI Salafiyah Tajungsari students have experienced language development according to their age and literacy literacy has also been classified as high, only that facilities and infrastructure still need improvement.